Changes in futsal activity profiles in a multiday tournament - Dogramaci, S.; Watsford, M.; Murphy, A. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: This study aimed to quantify the activity profiles of futsal players during a tournament, and detect changes in performance towards the final matches, focusing on changes in high-intensity activity.